International legal determination of the national minorities’ status in the Central and Eastern European countries within the Versailles system - G. G. Dedurin (Bulletin of Kharkiv National University of Internal Affairs)
Peculiarities of the international legal status determination of the national minorities within the Versailles system have been studied using the example of a number of Central and Eastern European countries. The governments of Czechoslovakia, Poland, and Hungary were asked, based on the norms of international law, to develop appropriate provisions for the protection of the rights of national minorities in order to prevent new conflicts and threats to peace.